Rawls's egalitarianism - Kaufman, Alexander, 1958- (Cambridge : Cambridge University Press, 2018)
A new analysis of John Rawls's theory of distributive justice, focusing on the ways his ideas have both influenced and been misinterpreted by the current egalitarian literature.
9 Poverty, Inequality, and JusticeReferences; Index.
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed June 08, 2018).
eBooks on EBSCOhost
Keywords: Rawls, John, -- 1921-2002.; Rawls, John, -- 1921-2002; Justice; Justice; POLITICAL SCIENCE -- Government -- General; Justice